2020
DOI: 10.1109/access.2020.3008327
|View full text |Cite
|
Sign up to set email alerts
|

Where are You? Exploring Micro-Location in Indoor Learning Environments

Abstract: Classroom teaching methodologies are gradually changing from masterclasses to active learning practices, and peer collaboration emerges as an essential skill to be developed. However, there are several challenges in evaluating collaborative activities more objectively, as well as to generate valuable information to teachers and appropriate feedback to students about their learning processes. In this context, multimodal learning analytics facilitate the evaluation of complex skills using data from multiple data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In contrast, the models outperformed the baseline model regarding each collaboration assessment item (T4–T6) with an acceptable level of differentiation (Hosmer Jr et al, 2013) (AUC of around 0.74). This finding was expected as students' spatial behaviours has been frequently found to contain meaningful insights about their interaction and collaboration in physical learning spaces (Riquelme et al, 2020; Saquib et al, 2018; Yan et al, 2021). Whereas in Scenario B (Table 4), the models performed poorly for every assessment item with low AUC and large variability.…”
Section: Resultsmentioning
confidence: 85%
“…In contrast, the models outperformed the baseline model regarding each collaboration assessment item (T4–T6) with an acceptable level of differentiation (Hosmer Jr et al, 2013) (AUC of around 0.74). This finding was expected as students' spatial behaviours has been frequently found to contain meaningful insights about their interaction and collaboration in physical learning spaces (Riquelme et al, 2020; Saquib et al, 2018; Yan et al, 2021). Whereas in Scenario B (Table 4), the models performed poorly for every assessment item with low AUC and large variability.…”
Section: Resultsmentioning
confidence: 85%
“…Most of the MMLA research (n=83) did not include any information about the ethical issues of the technologies used in MMLA research. Among the 13 studies that have included ethical-related information, two studies [9,60] only briefly mentioned ethical concerns in the introduction or the literature review section but did not elaborate on the ethical implications of the technologies used in the research. In the remaining 11 studies, we have identified three major ethical challenges, including privacy, equality, and risks of bias.…”
Section: Ethical Challenges -Rq3mentioning
confidence: 99%
“…Wearable tracking devices have also demonstrated potentials in generating insights about different types of student interactions [10]. Riquelme et al [40] used beacons to track the movement and interaction patterns of students with other student groups and various objects within a library. Through clustering and pattern analysis, these positioning data provide insights about potential collaborative learning behaviours under experimental conditions.…”
Section: Indoor-sensing Technologies and Learning Analyticsmentioning
confidence: 99%
“…These approaches have utilised various forms of technologies and data sources, including WiFi data [35], computer vision algorithms [1,6], thermal sensors [7], and wearable technologies [30,42]. They have also focused on a range of learning spaces, such as small fabrication rooms [9], healthcare simulation rooms [12], the library [40], laboratories [30], regular classrooms [1,42], and lecture rooms [6]. Out of these approaches, physical positioning tacking is one of the promising methods in providing fine-grained data for capturing in-class social interactions because of its high spatial-temporal precision [30].…”
Section: Introductionmentioning
confidence: 99%